BIODEGRADATION OF BIFENTHRIN PESTICIDE BY INDIGENOUS BACTERIA FROM PESTICIDE CONTAMINATED SOIL - A.S. PAWAR; G. V. MALI; H. V. DESHMUKH (International Journal of Pharma and Bio Sciences, 2016)
Pyrethroid group of pesticide is extensively used in agriculture, animal health, home, and garden pest control. Bifenthrin [2-methylbiphenyl-3-ylmethyl-(Z)-(1RS) - 3 -2-chloro-3,3,3 trifluoro- prop -1-enyl)-2,2 dimethylcyclopropane carboxylate] is one of the pesticide among the pyrethroids group of pesticides, which is effective against a broad spectrum of insect pests of economically important crops. It has been considered as greatest toxic component. The present work deals with the biodegradation of bifenthrin by using indigenous bacteria isolated from contaminated soil. It describes the biodegradation of bifenthrin by bacterial isolate IK2a into nontoxic metabolites like benzene 1, 1(methylthio) ethylidine, resorcinol and monochlorotrifluromethane which was confirmed by FTIR and GCMS analysis.